ASSESSING THE EFFICACY OF CLOUD SERVICES FOR DEVELOPING EDUCATIONAL PRESENTATIONS - Tetiana V. Bondarenko; Nadia M. Stetsenko; Volodymyr P. Stetsenko; Halyna V. Tkachuk (Інформаційні технології і засоби навчання)
The article examines the most popular cloud services for creating educational presentations and seeks to determine the effectiveness of their integration within the educational framework. A webometric analysis of these cloud services resulted in the identification of the top 10 resources commonly employed for presentation creation, including Prezi, Sway, Slides, PowToon, Canva, ZohoShow, Genial.ly, Emaze, Piktochart, VideoScribe, among others. Our research conducted a comprehensive comparative analysis of these platforms, utilizing web analytics tools such as Ahrefs, Moz, and Similarweb to establish their respective rankings. This approach facilitated an encompassing selection of cloud-based educational tools capable of meeting the multifaceted requirements of all stakeholders in the educational process.